The impact of early percutaneous endoscopic gastrostomy placement on treatment completeness and nutritional status in locally advanced head and neck cancer patients receiving chemoradiotherapy - ATASOY, BESTE MELEK; DANE, FAYSAL; YILMAZ, YUSUF (SPRINGER, 2012)
To investigate the impact of early insertion of percutaneous endoscopic gastrostomy-tube on nutritional status and completeness of concurrent chemotherapy in locally advanced head and neck cancer patients treated with chemoradiotherapy. Twenty-three patients were enrolled into this prospective study. Gastrostomy-tube was inserted in patients before the initiation of chemoradiotherapy. There was not any significant change in nutritional parameters of patients that used their tube during treatment. Despite the grade 3 mucositis, the planned concurrent chemotherapy could be given in 70% of the patients. However, nine patients had weak compliance and their body weight (P = 0.01) and body mass index (P = 0.01) deteriorated in the first 4 weeks of chemoradiotherapy. The completeness of concurrent chemo-rate was 44% in these patients. Toxicity, requiring aggressive supportive care, may limit the chemotherapy part of curative concomitant chemoradiotherapy. By providing adequate enteral nutrition the insertion of gastrostomy-tube can increase the completeness rate of concurrent chemotherapy.
Keywords: Chemoradiotherapy; Enteral nutrition; Gastrostomy; Head and neck neoplasms; QUALITY-OF-LIFE; WEIGHT-LOSS; CONCOMITANT CHEMORADIOTHERAPY; STAGE-III; RADIOTHERAPY; PREDICTORS; CARCINOMA; TUBES; INTERVENTION; CHEMOTHERAPY